An expansion of intelligent systems complex for express-diagnostics and prevention of organizational stress, depression, and deviant behavior on the basis of the biopsychosocial approach - Yankovskaya, A. E.; Kornetov, A. N.; Il’inskikh, N. N.; Obukhovskaya, V. B. (Pattern recognition and image analysis, 2017)
The paper is devoted to the extension of the intelligent systems complex for express-diagnostics consisting of express-diagnostics systems of organizational stress (DIOS), depression (DIAPROD), and deviant behavior (DIDEV) by the addition of a system of express-diagnostics designed for diagnosis of anxiety (DIAA). Application of the extended complex of intelligent systems of express-diagnostics of organizational stress, depression, deviant behavior, and anxiety (ISED OSDDA) will make it possible to promptly make diagnostic, preventative medical, and organizational-management decisions on the aforementioned disorders on the basis of the biopsychosocial approach; to justify these decisions with the use of graphic (including cognitive) tools; and to make complex decisions on the subject under investigation.